Below Knee Stump Reconstruction with a Foot Fillet Flap - Tos, Pierluigi; Antonini, Andrea; Pugliese, Pierfrancesco; Panero, Bernardino; Ciclamini, Davide; Battiston, Bruno (Journal of Reconstructive Microsurgery, 2017)
Background The “spare parts” approach to the reconstruction of below knee amputation, applied in acute trauma patients, can also be employed in elective surgery, ensuring knee salvage and a sensitive stump and enabling tissue harvesting without further donor-site morbidity.Methods We present a series of eight cases, where leg amputation due to trauma or its sequelae was followed by reconstruction with skin or a composite flap from the foot. An osteocutaneous flap was used in two emergency patients with below knee amputation, where it allowed stump elongation and knee coverage, and in five secondary procedures, where it provided both stump length and sensitive skin coverage. The skin of the foot was used in one case to cover the tibial stump. Fixation was accomplished with 2-mm Kirschner wires in the emergency patients and with an external fixator (n = 5) or by internal fixation (n = 1) in the elective procedures. Any complications were minor. Secondary compression with an external fixator was required in one emergency patient due to delayed bone healing.Results All knees healed. Sensibility was restored in all patients with a posterior tibial nerve suture (S4) and was well preserved in those without nerve coaptation. No patients reported problems with the prosthesis at a minimum follow-up of 3 years. Knee flexion and extension were comparable to those of the contralateral limb.Conclusion The “spare parts” concept is a reliable approach to tibial stump reconstruction. External fixation in elective procedures allowed immediate weight bearing and bone healing. In emergency patients, rapid fixation with wires provided satisfactory results.
Keywords: fillet flap; spare parts; below knee stump reconstruction; lower limb replantation